Organization theory : historical-theoretical development and the implications of technology - Van Niekerk, Chris (Not Specified, 2024)
[page 29 missing] Organization Theory has developed into what has become an interdisciplinary, quasi-independent field of study. It has as its objective the study of the structure and functioning of organizations, and the behaviour of groups and individuals within them. This area of study has, through the years, drawn the attention of writers from diverse backgrounds and with diverse interests. The first focus of this thesis is an examination of the historical and theoretical threads which have contributed to organizational studies. The path followed moves through the following stages : (1) classical theory, (2) scientific management, (3) human factor industrial psychology, (4) the human relations movement, and (5) organizational psychology or "nee-human relations". This thesis looks at landmark contributions, emphasizing the distinct approach, choice of problems, methodology and social attitudes of the proponents. Each stage is characterized by its underlying assumptions concerning the nature of man, ranging from the homo oeaonomiaus of the Taylorians, to the "Complex Man" of writers such as Schein and Bennis. This "pattern" of ... increasing sophistication is further illustrated by the shift from the limited concerns of early writers, for example, the human relationists'concentration on informal social relationships, to more comprehensive analytical schemes. A further feature of this movement is the inclusion by more contemporary writers of the role of organizational environments in their analyses, an area often neglected. This development culminates in a "reconceptualization" of organizations as systems and it is shown that a systems scheme offers distinct advantages in comparison to previous more limited perspectives